2022
DOI: 10.1002/pat.5607
|View full text |Cite
|
Sign up to set email alerts
|

Schiff base fluorescent hydrogel containing acylhydrazone structure and pyridine ring with multifunction

Abstract: In order to prepare multifunctional fluorescent hydrogel (FH), functional Schiff base ligands have been incorporated into polymer networks. We reported here a novel multifunctional Schiff base functionalized FH, P(AM-PEGA-PEPMA), and its corresponding metallohydrogel, Zn 2+ -P(AM-PEGA-PEPMA), which exhibited tunable fluorescence intensity, self-healing ability, stretchability, and shape-memory property. P(AM-PEGA-PEPMA) was obtained by one-pot micellar copolymerization and Zn 2+ -P(AM-PEGA-PEPMA) was formed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The indole‐containing Schiff base has been extensively studied for its fluorescence and antibacterial properties, 33,34 and the indole‐containing ring contains “NH” bond, which facilitates its synergistic effect in multiple hydrogen bonds and hydrophobic association mechanism to a certain extent. Our group reported that Schiff base hydrogels containing pyridyl hydrazone structure had excellent mechanical properties, pH response and fluorescence regulation 35,36 . Our group also reported the ultra‐stretchable and self‐healing hydrogels, which had excellent fatigue resistance, viscosity and electrical conductivity, and they could be used in flexible strain sensors 37 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The indole‐containing Schiff base has been extensively studied for its fluorescence and antibacterial properties, 33,34 and the indole‐containing ring contains “NH” bond, which facilitates its synergistic effect in multiple hydrogen bonds and hydrophobic association mechanism to a certain extent. Our group reported that Schiff base hydrogels containing pyridyl hydrazone structure had excellent mechanical properties, pH response and fluorescence regulation 35,36 . Our group also reported the ultra‐stretchable and self‐healing hydrogels, which had excellent fatigue resistance, viscosity and electrical conductivity, and they could be used in flexible strain sensors 37 .…”
Section: Introductionmentioning
confidence: 93%
“…Our group reported that Schiff base hydrogels containing pyridyl hydrazone structure had excellent mechanical properties, pH response and fluorescence regulation. 35,36 Our group also reported the ultra-stretchable and self-healing hydrogels, which had excellent fatigue resistance, viscosity and electrical conductivity, and they could be used in flexible strain sensors. 37 In the previous work of our group, 38 the mechanical properties of hydrogels were enhanced by adding chemical cross-linkers, while the work in this paper only relied on the synergistic effect of non-covalent bonds to achieve the toughening of hydrogels.…”
Section: Introductionmentioning
confidence: 98%
“…In order to construct multifunctional metal-coordinated hydrogels easily, we developed the hydrogels by introducing functional Schiff base ligands into the polymer network. For example, we reported two self-healing and multi-stimulus-responsive hydrogels by functional Schiff base ligands. On this basis, we reported a transparent, stretchable, self-healing, adhesive hydrogel sensor that could transmit fluorescent information in this work.…”
Section: Introductionmentioning
confidence: 99%